A comparative study of spin coated and floating film transfer method coated poly (3-hexylthiophene)/poly (3-hexylthiophene)-nanofibers based field effect transistors - Tiwari S.; Takashima W.; Nagamatsu S.; Balasubramanian S.K.; Prakash R. (My University, 2025)
A comparative study on electrical performance, optical properties, and surface morphology of poly(3-hexylthiophene) (P3HT) and P3HT-nanofibers based "normally on" type p-channel field effect transistors (FETs), fabricated by two different coating techniques has been reported here. Nanofibers are prepared in the laboratory with the approach of self-assembly of P3HT molecules into nanofibers in an appropriate solvent. P3HT (0.3 wt. %) and P3HT-nanofibers (∼0.25 wt. %) are used as semiconductor transport materials for deposition over FETs channel through spin coating as well as through our recently developed floating film transfer method (FTM). FETs fabricated using FTM show superior performance compared to spin coated devices; however, the mobility of FTM films based FETs is comparable to the mobility of spin coated one. The devices based on P3HT-nanofibers (using both the techniques) show much better performance in comparison to P3HT FETs. The best performance among all the fabricated organic field effect transistors are observed for FTM coated P3HT-nanofibers FETs. This improved performance of nanofiber-FETs is due to ordering of fibers and also due to the fact that fibers offer excellent charge transport facility because of point to point transmission. The optical properties and structural morphologies (P3HT and P3HT-nanofibers) are studied using UV-visible absorption spectrophotometer and atomic force microscopy, respectively. Coating techniques and effect of fiber formation for organic conductors give information for fabrication of organic devices with improved performance. © 2014 AIP Publishing LLC.